Influence of physical maturity status on sprinting speed among youth soccer players - McCunn, R.; Weston, M.; Hill, J. K. A.; Johnston, R. D.; Gibson, N. V. (The Journal of Strength and Conditioning Research, 2017)
The relative age effect is well documented with the maturation-selection hypothesis the most common explanation; however, conflicting evidence exists. We observed the birth date distribution within an elite junior soccer academy. The influence of physical maturity status on anthropometric variables and sprinting ability was also investigated. Annual fitness testing was conducted over an 8-year period with a total of 306 players (age: 12.5 ± 1.7 years [range: 9.7-16.6 years]; stature: 156.9 ± 12.9 cm; mass: 46.5 ± 12.5 kg) drawn from 6 age categories (under-11s to under-17s) who attended the same Scottish Premiership club academy. Measurements included mass, stature, maturity offset and 0-15 m sprint. Odds ratios revealed a clear bias toward recruitment of players born in quartile 1 compared with quartile 4. The overall effect (all squads combined) of birth quartile was very likely small for maturity offset (0.85 years; 90% confidence interval [CI], 0.44-1.26 years) and stature (6.2 cm; 90% CI, 2.8-9.6 cm), and likely small for mass (5.1 kg; 90% CI, 1.7-8.4 kg). The magnitude of the relationship between maturity offset and 15-m sprinting speed ranged from trivial for under-11s (r = 0.01; 90% CI, -0.14 to 0.16) to very likely large for under-15s (r = -0.62; -0.71 to -0.51). Making decisions about which players to retain and release should not be based on sprinting ability around the under-14 and under-15 age categories because any interindividual differences may be confounded by transient inequalities in maturity offset.